Facing death in the intensive care unit: the nurse’s awarenesses - Maria Edilene Nunes Fernandes; Ana Fátima Carvalho Fernandes; Ana Lúcia Pereira de Albuquerque; Maria Lurdemiller Sabóia Mota (Rev Rene)
It is still very difficult for nurses to face death and this fact has made them feel worried, due to their lack of ability to deal with this process. The aim of this study was to identify the understanding of the nurse who in the Intensive Care Unit (UTI), about the death process and the experiencing of patients’ death. The exploratory descriptive methodology was used, through the interview technique applied to eight nurses, four of which worked in public institutions and four, in private service companies, all located in the city of Fortaleza in 2002. The analysis of the speeches convergence allowed the identification of some meaning units such as: understanding death, experiencing and dealing with patients’ death. This study will contribute to the practice of nursing undergraduate courses’ professors, leading them to rethink the importance of tanatology as a permanent subject of discussion, during the professional formation process.